Characterization of human iPSC-derived astrocytes with potential for disease modeling and drug discovery. (13th July 2020) - Soubannier, Vincent; Maussion, Gilles; Chaineau, Mathilde; Sigutova, Veronika; Rouleau, Guy; Durcan, Thomas M.; Stifani, Stefano
Highlights: Astrocytes were derived from human induced pluripotent stem cells (hiPSC-astrocytes). hiPSC-astrocytes exhibit properties typical of physiological astrocytes. hiPSC-astrocytes display spontaneous and induced calcium transients. hiPSC-astrocytes acquire a reactive phenotype in response to proinflammatory stimuli. hiPSC-astrocytes are a suitable system to investigate astrogliosis in human astrocytes. Abstract: Astrocytes play a number of key functions in health and disease. Activated astrocytes are present in most, if not all, neurological diseases. Most current information on the mechanisms underlying reactive astrocyte emergence derives from studies using animal experimental systems, mainly because the ability to study human astrocytes under healthy and pathological conditions has been hampered by the difficulty in obtaining primary human astrocytes. Here we describe robust and reliable derivation of astrocytes from human induced pluripotent stem cells (iPSCs). Phenotypically characterized human iPSC-derived astrocytes exhibit typical traits of physiological astrocytes, including spontaneous and induced calcium transients. Moreover, human iPSC-derived astrocytes respond to stimulation with a pro-inflammatory combination of tumor necrosis factor-alpha, interleukin 1-alpha, and complement component C1q by undergoing changes in gene expression patterns suggesting acquisition of a reactive astrocyte phenotype. Together, these findings provide evidence suggesting that human iPSC-derived astrocytes are a suitable experimental model system to study astrocyte function and reactivation in healthy and pathological conditions of the human nervous system.